2021
DOI: 10.1021/acscatal.1c00687
|View full text |Cite
|
Sign up to set email alerts
|

Local Electric Fields As a Natural Switch of Heme-Iron Protein Reactivity

Abstract: Heme-iron oxidoreductases operating through the high-valent FeIVO intermediates perform crucial and complicated transformations, such as oxidations of unreactive saturated hydrocarbons. These enzymes share the same Fe coordination, only differing by the axial ligation, e.g., Cys in P450 oxygenases, Tyr in catalases, and His in peroxidases. By examining ∼200 heme-iron proteins, we show that the protein hosts exert highly specific intramolecular electric fields on the active sites, and there is a strong correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 59 publications
2
61
0
Order By: Relevance
“…Recently, we have demonstrated that heme-iron proteins exert highly specific intramolecular electric fields on their active sites and that there is a strong correlation between the direction and magnitude of this field and the protein function. 44 Herein, we demonstrate that the local electric fields produced by the proteins of the BC family are likewise not randomly oriented and instead appear customized by the evolution to fine-tune the BC centers' properties. This includes modifying the BC site geometry, electronic structure, BC spectral features, and Cu( ii / i ) reduction potentials.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, we have demonstrated that heme-iron proteins exert highly specific intramolecular electric fields on their active sites and that there is a strong correlation between the direction and magnitude of this field and the protein function. 44 Herein, we demonstrate that the local electric fields produced by the proteins of the BC family are likewise not randomly oriented and instead appear customized by the evolution to fine-tune the BC centers' properties. This includes modifying the BC site geometry, electronic structure, BC spectral features, and Cu( ii / i ) reduction potentials.…”
Section: Introductionmentioning
confidence: 87%
“…The QM/MM studies on the system show that an electric field applied along the Fe−Cl bond reduces the charge on chloride and thus increases its radical character, which facilitates Cl recombination [144,145] . The role of electric field (both external and induced by the protein) in reaction selectivity of heme enzymes was also observed and described [146–148] …”
Section: The Wealth Of Odd‐catalysed Reactions and The Inherent Prope...mentioning
confidence: 93%
“…[144,145] The role of electric field (both external and induced by the protein) in reaction selectivity of heme enzymes was also observed and described. [146][147][148]…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Enzyme active sites leverage effects such as hydrogen bonding, electron transfer pathways, and electrostatic effects to precisely tune the reactivity of metallocofactors. 1 , 2 , 11 , 3 10 One example illustrating the importance of the secondary coordination sphere is in oxidase chemistry. For example, the terminal oxidant in cytochrome P450 enzymes, Compound I, consists of an Fe(IV)-oxo which is generated from O 2 via the delivery of proton and electron equivalents from cofactors and the protein superstructure.…”
Section: Introductionmentioning
confidence: 99%